Clinical Fitting and Adjustment Time for Implant‐Supported Crowns Comparing Digital and Conventional Workflows. (22nd September 2015) - Joda, Tim; Katsoulis, Joannis; Brägger, Urs
Abstract: Purpose: The aim of this prospective cohort study was to investigate clinical and laboratory performance of implant‐supported reconstructions comparing the digital to the conventional workflow. Materials and Methods: Twenty study participants were treated in a cross‐over design for single‐tooth replacement in posterior sites, each with a customized titanium abutment plus computer‐assisted design and computer‐assisted manufacturing (CAD/CAM)‐zirconia‐suprastructure (test: digital workflow; n  = 20) and a standardized titanium abutment plus PFM‐crown (control: conventional pathway; n  = 20). Evaluation of the 40 reconstructions included: 1) feasibility of laboratory cross‐mounting of each abutment‐crown‐connection, and 2) assessment of adaptation time for clinical adjustments of interproximal and occlusal surfaces. Statistical analyses were performed using the exact W ilcoxon   r ank   s um   t ests . Results: Laboratory cross‐mounting was feasible for three reconstruction pairings revealing a 15% vice versa transfer success rate. All implant crowns could be provided successfully within two clinical appointments, independently of the workflow used. The mean clinical adjustment time was significantly lower ( p  < .001) for test reconstructions from the digital workflow with 2.2 min (standard deviation [SD] ± 2.1) compared with the ones from the conventional pathway with 6.0 min (SD ± 3.9). Conclusions: The digital workflow was almost threefold more efficient than the established conventional pathway for fixed implant‐supported crowns. Clinical fitting could be predictably achieved with no or minor adjustments within the digital process of intraoral scanning plus CAD/CAM technology.